Alkaloids from the Malayan Hunteria zeylanica Gard. - Awang, Khalijah; Ismail, Nor Hadiani; Velu, Saraswati S.; Thomas, Noel F.; F. Weber, Jean-Frederic; A. Hadi, A. Hamid (Malaysian Journal of Science, 2009)
A phytochemical study on Hunteria zeylanica Gard from the Malayan flora was conducted resulting in the isolation and characterization of six alkaloids. Five of them were indole alkaloids, which are eburnamine, isoeburnamine, eburnamenine, yohimbol and eburnamonine. In addition a venoterpene which contain a pyridine nucleus was also isolated. Structural elucidation of the compounds was accomplished by modern spectroscopic techniques: 2D NMR, IR, UV and MS.